2021
DOI: 10.1088/1361-6587/abdc9b
|View full text |Cite
|
Sign up to set email alerts
|

Transport model of plasma heating at the second harmonic of the electron cyclotron frequency

Abstract: The optical thickness of the plasma is often insufficient to fully absorb the microwaves during heating at the second harmonic of the electron cyclotron frequency. An analysis of the experiments to the T-10 tokamak allows us to find the criteria for the full absorption, and to construct a canonical profile transport model for the full and partial absorptions of microwaves. The conditions to the equivalence of discharges in different tokamaks, and in a pair of tokamaks with the optimized W7-X stellarator are fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Its frequency and the wavenumber obey the quantization condition (8). We assume that the y component of the LH or EP wavenumber is equal to the value determined by equation (10). At the PDI onset, the amplitude Φ p,r of the nonlinearly excited LH or EP wave begins to rise in the pump localization zone and to experience diffraction along y.…”
Section: The O-mode Induced Scattering Off the 2d Localized Lh Or Ep ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Its frequency and the wavenumber obey the quantization condition (8). We assume that the y component of the LH or EP wavenumber is equal to the value determined by equation (10). At the PDI onset, the amplitude Φ p,r of the nonlinearly excited LH or EP wave begins to rise in the pump localization zone and to experience diffraction along y.…”
Section: The O-mode Induced Scattering Off the 2d Localized Lh Or Ep ...mentioning
confidence: 99%
“…Over the last decade and a half, however, a number of anomalous phenomena have been detected in ECRH experiments on various toroidal devices. These include anomalous microwave backscattering [5][6][7], ion acceleration [8,9], an evident broadening of the ECRH power deposition profile [10,11] and radiation at sub-harmonics of the gyrotron frequency [12]. Anomalous effects have been consistently observed at ECRH power levels well below the threshold of various nonlinear phenomena that can accompany microwave propagation in inhomogeneous plasma [4], but only in the presence of a non-monotonic (hollow) plasma density profile, often observed in ECRH experiments [13].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the energy transport in a tokamak using a critical gradient transport model [2] showed that the right hand side of this ratio should be increased by some factor [3]. In [4] we determine this factor and use the following relation:…”
Section: Introductionmentioning
confidence: 99%
“…Plasma heating using ECR waves at the second harmonic X-mode (X2 ECRH) is discussed in [4], where criteria for full or partial absorption were derived, the concept of equivalent pairs of tokamak and stellarator discharges was introduced, and the necessary and sufficient conditions for equivalence were formulated. As an example of equivalent pairs, we have used, on one hand, experimental discharges from the W7-X stellarator, and, on the other hand, the modelling results for the T-15MD tokamak using the Standard transport model of canonical profiles (STMCP).…”
Section: Introductionmentioning
confidence: 99%
“…Such a system is also discussed for DEMO. However, over the last decade a number of anomalous phenomena -anomalous microwave backscattering [8,9], ion acceleration [10,11], an evident broadening of the ECRH power deposition profile [12,13] and radiation at sub-harmonics of the gyrotron frequency [14] -were discovered in ECRH experiments in different toroidal devices. The explanation of these observations turned out to be impossible within the framework of the traditional theoretical model [7].…”
mentioning
confidence: 99%